Analisis kesulitan belajar pemecahan masalah matematika berdasarkan newman procedure pada peserta didik kelas v sekolah dasar - Deanisa Adilla Putri; Retno Winarni; Anesa Surya (Universitas Sebelas Maret, 2021)
This article aims to describe the student’s learning difficulties in learning problem solving based Newman procedures on the 5th grade students of Bratan 1 Surakarta Elementary School in the academic year 2020/2021. The method used in this research is descriptive qualitative. The subjects were six students class of 5A at Bratan 1 Surakarta Elementary School. Data collection techniques through interview, research’s documentation, and questionnaire. Validity that used are triangulation techniques. Techniques of analyzing data of this research is using interactive analysis. The results of this research indicate students have difficulty in problem solving process skills steps. This research will assist teachers in developing innovative learning to reduce the student’s learning difficulties in problem solving.